Geografia dos campeões: migração, força de trabalho e nacionalidade de argentinos e franceses na Copa do Mundo do Catar 2022 - Mateus de Almeida Prado Sampaio; Igor Breno Barbosa de Sousa; Elvis Simões Pitoco da Silva (Confins)
The 2022 Men's Football World Cup in Qatar has attracted attention due to the multinationality of the players and the transnational composition of the participating teams. The aim of this article is to promote a debate around this sport as a face of the current stage of globalization, breaking with the borders of the past and interlinking migratory flows of the workforce with the question of the nationality (or dual nationality) of the players. We worked based on the two finalist teams, Argentina and France, because of their notable differences in terms of the place of birth and citizenship of their players. We believe that football increasingly reflects the effects of a globalized world in which economic power is progressively felt in the professional lives of football stars. Cartographic production is an important methodological step in this work.